2017
DOI: 10.4028/www.scientific.net/ddf.380.72
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Industrial Hollow Ceramic Brick: Analysis of the Moisture Content and Temperature Parameters

Abstract: The study of ceramic drying is theme of several researches today. In most case, this research is realized experimentally, making possible measurements errors that reverberating in data slightly out of the expected, or erroneous. Numerical simulation emerges like a tool that allows the reproduction of experiments using computers and suitable software’s. The use of numerical simulation enables fast changes in boundary conditions and help in the improvement of an unit operation. This paper aims to predict the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A mathematical model used for simulation of roof tiles in the kiln manufacturing process was introduced [19]. The experimental results revealed that the required mean flow velocity must be in the range of 20 m/s by using tiles of roofs showing specific numerical simulation to envisage moisture contents, temperature profile in the hollow setting of ceramic bricks during the procedure of drying in industry [20]. In the preheating zone of the tunnel kiln two axial flows in mixing ware by means of side nozzle is examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical model used for simulation of roof tiles in the kiln manufacturing process was introduced [19]. The experimental results revealed that the required mean flow velocity must be in the range of 20 m/s by using tiles of roofs showing specific numerical simulation to envisage moisture contents, temperature profile in the hollow setting of ceramic bricks during the procedure of drying in industry [20]. In the preheating zone of the tunnel kiln two axial flows in mixing ware by means of side nozzle is examined.…”
Section: Introductionmentioning
confidence: 99%
“…AC induction motors usually work with a load much less as compared to their maximum rating. Many surveys show that the average load factor for these motors is 57-68% of their ratings, and machine often operate with more less load, even in between 3-16% [20]. It was observed that 44% of motors installed in industrial sector are loaded at less than 40% of their rated power [26].…”
Section: Introductionmentioning
confidence: 99%
“…Its purpose is to identify better drying conditions (optimized process), with less process time, in order to reduce or eliminate dry material waste, by using a CFD analysis. The authors have contributed to the numerical study of the drying ceramic brick considering the mass and heat transfer and fluid flow in the air around the solid in previous works [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…If the drying process is not performed correctly, it can lead to material defects, loss of productivity, and increase in the energy consumption. According to the literature [6][7][8][9][10][11][12][13][14][15][16][17][18], the operating variables that influence the drying process are temperature, relative humidity and velocity of the drying air, time, shape, thickness, area/volume ratio, particle size, initial moisture content, and properties of the ceramic material.…”
Section: Introductionmentioning
confidence: 99%